Responsibility in International Law - Volker Roben (Max Planck Yearbook of United Nations Law, 2012)
ABSTRACTInternational legal materials refer to ‘common but differentiated responsibility’, the ‘responsibility to protect’, or the ‘responsibility for the global economy’. These terms are manifestations of a single institution of international responsibility, which undergirds much of international law development since the 1990s. Institutions combine an idea and a legal reality. The idea of responsibility is that it establishes a relation between the vectors of moral agent, object, addressee to which the agent is accountable, and criteria of assessment. In the context of international law, states are the primary agents of responsibility, with international organisations being assigned with secondary responsibility. Accountability generally lies to the international community, acting through appropriate bodies which assess whether actors meet their assigned responsibility according to defined standards. This matrix of international responsibility is normatively guaranteed and concretised through an international law-making process that proceeds from the recognition in a non-binding document of responsibility as foundational principle for an area of law to the development of binding treaty law and alternative means of international law-making. The thus conceptualised institution of international responsibility is then shown to manifest itself in three reference areas of international law: sustainable development, international financial markets, and state-internal peace and stability including the responsibility to protect civilians. The paper concludes by drawing normative implications for the development and interpretation of international law that falls within the ambit of the institution of international responsibility.